2009
DOI: 10.1177/0883073809343315
|View full text |Cite
|
Sign up to set email alerts
|

Early Testing for Huntington Disease in Children: Pros and Cons

Abstract: We report 2 young children who are examples of the consequences of premature testing for Huntington disease. Premature testing of a child or fetus carries complex medical and psychological issues to both the child and the family that need to be considered and explored more than in an adult with Huntington disease. We suggest that a child at risk for juvenile Huntington disease not be tested until symptoms are progressive and consistent with the disease and all other mimickers are excluded. When testing is indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, it is possible, though unlikely based on our findings, that a child with symptoms suggestive of JHD, a positive family history, and a pathologic expansion has in fact an alternative diagnosis. 5,6 With long and careful follow-up, however, the clinician should be able to unequivocally attribute the symptoms to JHD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it is possible, though unlikely based on our findings, that a child with symptoms suggestive of JHD, a positive family history, and a pathologic expansion has in fact an alternative diagnosis. 5,6 With long and careful follow-up, however, the clinician should be able to unequivocally attribute the symptoms to JHD.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Clinical features of JHD, which often include rigidity, cognitive decline, and behavioral disturbance, are more varied, less specific, and also found in other early-onset neuropsychiatric disorders, suggesting diagnosis may be challenging in the absence of a family history of HD. 3,5 Alternatively, the presence of family history in a child with suggestive symptoms may not necessarily mean they are caused by JHD. 5,6 To date, there are no established rules to guide clinicians contemplating genetic testing in a child with suspected HD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-symptomatic genetic testing may have occurred in children whose parents are known to carry the disease. However, the appropriateness of testing young children who are unable to consent and for a condition with no cure is debatable [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the obvious ethical restriction in testing minors 15,16 , a rather limited number of studies have so far reported detailed clinical features of JHD 2,5,7,10,17 . However, epidemiological, demographic and clinical genetic studies of JHD in populations with different ethnic backgrounds may contribute to better understand the variability in the phenotype and frequency 5,9,13,18 .…”
mentioning
confidence: 99%